2019
DOI: 10.3390/nu11010169
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ketogenic Diets in Neurodegenerative Diseases (Alzheimer’s Disease and Parkinson’s Disease)

Abstract: The goal of this review was to assess the effectiveness of ketogenic diets on the therapy of neurodegenerative diseases. The ketogenic diet is a low-carbohydrate and fat-rich diet. Its implementation has a fasting-like effect, which brings the body into a state of ketosis. The ketogenic diet has, for almost 100 years, been used in the therapy of drug-resistant epilepsy, but current studies indicate possible neuroprotective effects. Thus far, only a few studies have evaluated the role of the ketogenic diet in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
200
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(224 citation statements)
references
References 52 publications
0
200
0
10
Order By: Relevance
“…The ketogenic diet has shown to have neuroprotective effects in the context of several neurodegenerative diseases, such as Alzheimer's, and Parkinson's disease [70]. The neuroprotective effect of the ketogenic diet has been hypothesized to be a result of the biochemical changes resulting from glycolytic inhibition, increased acetyl-CoA production, and formation of ketone bodies in the cell [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ketogenic diet has shown to have neuroprotective effects in the context of several neurodegenerative diseases, such as Alzheimer's, and Parkinson's disease [70]. The neuroprotective effect of the ketogenic diet has been hypothesized to be a result of the biochemical changes resulting from glycolytic inhibition, increased acetyl-CoA production, and formation of ketone bodies in the cell [71].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that different anatomical regions of the human retina are susceptible to oxidative stress, highlighting the importance of antioxidant availability in the retina [13]. Ketone bodies increase mitochondrial respiration via increased ATP production and reduce ROS formation by increasing NADH oxidation, thereby improving the efficiency of the mitochondrial respiratory chain complex [70]. Targeting the TCA cycle and fatty acid synthase pathway by acetyl-CoA production via the ketogenic diet led to increased global retinal visual function compared to controls by one month of age.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegeneration associates with abnormal glycolysis and attenuated glucose uptake and metabolism, and KD inhibits these changes via altered metabolic activity (Figure ) (Wlodarek, ). Ketone bodies provide neuroprotection via ATP generation and regulate NADPH/NADP ratio, GSH activity, mitochondrial permeability, and reduced glycolytic flux, apoptosis, and neuroinflammation, resulting in normal synaptic neurotransmission (Wlodarek, ). β‐hydroxybutyrate treatment and dietary restrain in calorie intake also reduce oxidative stress, neuronal apoptosis, and neuroinflammation and enhance generation of neurotrophins, such as BDNF, and neurotrophin‐3 and glial cell line‐derived neurotrophic factor that significantly relate with altered neuronal functions, particularly in the aging brain (Wlodarek, ).…”
Section: Kd and Neurodegenerationmentioning
confidence: 99%
“…β-hydroxybutyrate treatment and dietary restrain in calorie intake also reduce oxidative stress, neuronal apoptosis, and neuroinflammation and enhance generation of neurotrophins, such as BDNF, and neurotrophin-3 and glial cell line-derived neurotrophic factor that significantly relate with altered neuronal functions, particularly in the aging brain (Wlodarek, 2019).…”
Section: K D and Neurodeg Ener Ati Onmentioning
confidence: 99%
See 1 more Smart Citation